2015
DOI: 10.1021/acs.bioconjchem.5b00264
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Temperature-Responsive Protein–Polymer Bioconjugates

Abstract: We report a simple temperature-responsive bioconjugate system comprising superfolder green fluorescent protein (sfGFP) decorated with poly[(oligo ethylene glycol) methyl ether methacrylate] (PEGMA) polymers. We used amber suppression to site-specifically incorporate the non-canonical azide-functional amino acid p-azidophenylalanine (pAzF) into sfGFP at different positions. The azide moiety on modified sfGFP was then coupled using copper-catalyzed “click” chemistry with the alkyne terminus of a PEGMA synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 107 publications
1
71
0
1
Order By: Relevance
“…We ando ther researchers have demonstrated that the conjugation of proteins to thermally responsivep olymers could change the phase-transition temperatures of the polymers significantly. [21][22][23][24] The shift in the phasetransition temperature of PNIPAM in PPL nanogelsi sa ttributed to the incorporation of PPL molecules to the network structures and an increase in the hydrophilicity of the polymer. After coating with BSA, the endotherm of PNIPAM shifts to the high-temperature regime.…”
Section: Resultsmentioning
confidence: 99%
“…We ando ther researchers have demonstrated that the conjugation of proteins to thermally responsivep olymers could change the phase-transition temperatures of the polymers significantly. [21][22][23][24] The shift in the phasetransition temperature of PNIPAM in PPL nanogelsi sa ttributed to the incorporation of PPL molecules to the network structures and an increase in the hydrophilicity of the polymer. After coating with BSA, the endotherm of PNIPAM shifts to the high-temperature regime.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the GFP was conjugated to an alkyne-terminated PEG molecule grafted to a functionalized PDMS surface through CuAAC. 173 The sfGFP was genetically introduced with pAzF. 172 The pAzF was incorporated into two different sites of GFP.…”
Section: Other Applications Of Pegylationmentioning
confidence: 99%
“…171 A protein-PEG conjugate also served as a monomer to polymerize the generation of a fibrous structure. 173 5 Conjugation of other polymers to proteins Then, the pAzF-containing GFPs were copolymerized with dialkyn-terminated PEGs via CuAAC, generating a protein-based giant fibrous architecture.…”
Section: Other Applications Of Pegylationmentioning
confidence: 99%
“…Previous research focused on preparing bioconjugates were mainly based on proteins such as bovine serum albumin (BSA), ovalbumin, chymotrypsin, streptavidin, and green fluorescent protein . Hoffman and co‐workers carried out pioneering work on preparation of various protein–PNIPAm conjugates for regulation of enzyme activity, triggered release, and enzyme recovery .…”
Section: Introductionmentioning
confidence: 99%